2017
DOI: 10.1053/j.gastro.2017.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of 3 High-Level Disinfection and Sterilization Procedures for Duodenoscopes

Abstract: In a comparison of duodenoscopes reprocessed by sHLD, dHLD, or HLD/ETO, we found no significant differences between groups for MDRO or bacteria contamination. Enhanced disinfection methods (dHLD or HLD/ETO) did not provide additional protection against contamination. However, insufficient events occurred to assess our primary study end-point. ClinicalTrials.gov no: NCT02611648.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 21 publications
0
75
1
2
Order By: Relevance
“…Biofilms may contribute to the recovery of viable microorganisms post processing even when current guidelines are followed. 31,60 The bulk of the literature about the processing of duodenoscopes relates to the currently recommended guidelines of performing HLD. Recent studies show positive bacterial contamination of duodenoscopes after HLD 58,60-62 and double-HLD processing.…”
Section: Sampled Sitementioning
confidence: 99%
See 4 more Smart Citations
“…Biofilms may contribute to the recovery of viable microorganisms post processing even when current guidelines are followed. 31,60 The bulk of the literature about the processing of duodenoscopes relates to the currently recommended guidelines of performing HLD. Recent studies show positive bacterial contamination of duodenoscopes after HLD 58,60-62 and double-HLD processing.…”
Section: Sampled Sitementioning
confidence: 99%
“…31,35 A study by Snyder et al showed no significant difference between duodenoscopes processed by HDL, double HLD, or HLD combined with EO sterilization, with positive bacterial growth being detected following all three processing methods. 31 Terminal sterilization of duodenoscopes has been identified as a leading solution for improving duodenoscope processing outcomes since it offers a significantly greater margin of safety than HLD. [36][37][38] According to the Spaulding classification scheme, flexible gastrointestinal endoscopes are classified as semi-critical devices, in which case sterilization is recommended, or if this is not possible, processing using HLD at a minimum.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations